Daily field checking list by Walter Rosene, March 14, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Bob Walker, March 14, 1937. Also notes the first egg in the Great Horned Owl nest has hatched. Plustek--flatbed